Desain Pembelajaran Model Dick and Carey Pada Mata Pelajaran Pendidikan Agama Islam - Zezen Futuhal Aripin; Uus Ruswandi; Muhammad Abdul Aziz (Gunung Djati Conference Series, 2022)
A good learning process will give birth to quality students. The achievement of learning objectives is obtained through the use of appropriate and effective learning designs. This article aims to explore and explore Dick and Carey's learning design in Islamic Religious Education learning. This research is descriptive qualitative. The results of the study indicate that the Dick and Carey learning design is very appropriate to be used in the learning process that is oriented towards the skills of students.